FAKTOR YANG MEMPENGARUHI PENGGUNAAN ROKOK ELEKTRIK PADA KALANGAN PEROKOK DEWASA DI INDONESIA - Rahmani, Salma Nadia; Indawati, Rachmah (Jurnal Medikes (Media Informasi Kesehatan), 2024)
Indonesia is experiencing a tobacco epidemic, with smokers known to be the largest consumers of cigarettes. The increasing use of e-cigarettes among adults raises important public health concerns. E-cigarettes are as harmful as any other tobacco product. Awareness of this trend has sparked discussion about the reasons behind e-cigarette use among adult smokers. This study aimed to determine the factors influencing e-cigarette use among adults. This study used secondary data from the Global Adult Tobacco Survey (GATS) Indonesia 2021. The target population included all men and women aged 15 years or older. The data analysis used was logistic regression. The results showed that the variables that significantly influenced the use of e-cigarettes included nicotine addiction (p-value = 0.000), use in places where smoking is prohibited (p-value = 0.016), perception of e-cigarettes is not more dangerous than cigarettes (p-value = 0.002), e-cigarettes are cheaper than tobacco cigarettes (p-value = 0.000).